Republic of Fiji : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of Fiji. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with the Republic of Fiji highlights that economic activity slowed sharply in 2019 due to lower government spending, tighter domestic financial conditions, weak sentiment, and the global deceleration. The slowdown followed several years of relatively strong growth, boosted by reconstruction spending after a major cyclone in 2016, which resulted in rising external and fiscal imbalances. Fiscal space is now at risk and external vulnerabilities remain significant. Fiji has large investment needs to strengthen resilience to natural disasters and climate change. A key priority should be to rebuild fiscal buffers in a growth-friendly way to create space to respond to future natural disasters and to ensure public debt sustainability. Fiscal consolidation should focus on reining in current spending given limited scope for further revenue mobilization and the need for capital spending to improve resilience to climate change. Improvements in the business environment and in governance are essential to raise potential growth and boost private investment, and to enhance productivity and competitiveness.